Can medical residency keep young specialists in the place where they graduate? Cross-sectional and exploratory study of the first seven years after implementation of medical residency programs in the State of Tocantins, Brazil - Grandi, Giovanna Tandaya; Baldaçara, Raquel Prudente de Carvalho; Coutinho, Itágores Hoffman I Lopes Sousa; Baldaçara, Leonardo (São Paulo Medical Journal, 2022)
BACKGROUND: New medical schools and new medical residencies in Brazil, mainly in its interior, were opened under the justification of collaborating towards distribution of these healthcare professionals and specialist doctors across the national territory. However, this proposal did not guarantee that medical practitioners would become established in the place where they graduated and specialized. OBJECTIVE: To calculate, through interviews, how many specialists who graduated in the state of Tocantins stayed there after finishing their medical residency; and to analyze the factors that made them stay or leave the place. DESIGN AND SETTING: Cross-sectional exploratory study conducted at a Brazilian federal public higher education institution. METHODS: All graduates from medical residencies in Tocantins, who graduated between 2013 and 2019, were contacted by telephone and, after obtaining consent, an interview was conducted. The interviews took place between June 2020 and January 2021. RESULTS: The permanence of medical residency graduates in the state increased from 50% in an earlier study to 55.8% in the current study, thus showing a situation of stability. In addition, we detected some reasons for staying or not. In a multivariate analysis, only working in the state capital was related to staying in the state of Tocantins, showing a 5.6 times greater chance. CONCLUSIONS: The percentage of those who remained was just over 50%, even some years after implementation of the first programs. Most specialists remained working for the state health department, with a smaller proportion in municipal health departments, and were concentrated in the state capital.